Implications of drying temperature and humidity on the drying kinetics of seaweed - Ali, M.K.M. (American Institute of Physics Inc., 2017)
A Low Temperature and Humidity Chamber Test tested in the Solar Energy Laboratory, Faculty of Science and Technology, Universiti Kebangsaan Malaysia, Selangor, Malaysia. Experiments are attempted to study the effect of drying air temperature and humidity on the drying kinetics of seaweed Kappaphycus species Striatum besides to develop a model to estimate the drying curves. Simple method using a excel software is used in the analysis of raw data obtained from the drying experiment. The values of the parameters a, n and the constant k for the models are determined using a plot of curve drying models. Three different drying models are compared with experiment data seaweed drying at 30, 40, 50 and 60°C and relative humidity 20, 30 and 40 for seaweed. The higher drying temperatures and low relative humidity effects the moisture content that will be rapidly reduced. The most suitable model is selected to best describe the drying behavior of seaweed. The values of the coefficient of determination (R2), mean bias error (MBE) and root mean square error (RMSE) are used to determine the goodness or the quality of the fit. The Page model is showed a better fit to drying seaweed. The results from this study crucial for solar dryer development on pilot scale in Malaysia. © 2017 Author(s).